SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN METODE SAW (STUDI KASUS KELURAHAN JATIWARINGIN: SAW;Simple Additive Weighting;Villages;Employees;Achievers. - Sartika, Bella; Cahya Putri Buani, Duwi (LP2M Universitas Nurdin Hamzah, 2022)
Simple Addictive Weighting (SAW) method is a definition of the term weighted sum. From this method the basic concept is to determine a weighted summation of the performance rankings on each alternative used in each attribute. The assessment will be more precise because it is based on the value of criteria and the weight of preferences that have been determined. The purpose of this study is to analyze the results of calculations using a decision support system adrift of the selection of outstanding employees in JatiwaringinPondokgede Village as the end result becomes the best assessment. Based on calculations using the Simple Additive Weighting (SAW) method, researchers obtained the best employees as many as 7 people with the highest score obtained by 1. And get 5 employees with the lowest score. By applying the Simple Additive Weight (SAW) method through a more efficient employee performance selection process so that from the village side more quickly decide in choosing the performance of outstanding employees. Decision on the use of Simple Additive Weighting (SAW) methods in agencies and skilled and creative workforces. For 5 employees who get the lowest grades are expected to get more coaching. In order to create better behavior than that.